The Analysis of the Relationship between Undergraduate and Diploma Unemployment Level with the Number of Business Incubators of Universities in Indonesia - Solihin, Ismail; Novan Setiawan Nugraha, Deden; S. Marinda, Vina; Augustrianto, Agung (International Journal of Psychosocial Rehabilitation, 2020)
The number of unemployed universities in Indonesia originating from undergraduate and diploma levels is still high. Unemployment undergraduates and diplomas themselves can be divided into two categories: unemployed undergraduates and diplomas that come from college graduates who have an interest in entrepreneurship and who do not have an interest in entrepreneurship. Business incubators in various universities are more suitable to be directed at reducing the potential for undergraduate and diploma unemployment, which during their time became students who had an interest in entrepreneurship. Unfortunately, the number of tertiary business incubators in Indonesia is currently still limited; it’s only 80 universities having business incubators and tenants from the total of 4,504 tertiary units in Indonesia.